(untitled) (Tanzania Medical Journal, 2020)
Background Postnatal care (PNC) is essential for ensuring the optimal health of women and their newborns. In Africa, most mothers and newborn do not visit healthcare facilities following childbirth despite the fact that majority of maternal and neonatal deaths occur during this period. Regardless the the existence of several programs for improving maternal and child health, the utilization of PNC yet remains low. The objective of this study was to assess the experiences and perceptions of women on postnatal care services utilization. Methodology A qualitative study design was used. The study was conducted in Nachingwea district. Women who delivered children within one year before the study and reside in Nachingwea district were recruited from Nachingwea district hospital and Naipanga dispensary. The selection was based on their age, education and parity. IDIs and FGDs were used. Qualitative content analysis was used for analysis. Results Sixty-six (66) women who brought their babies to PNC services for immunization and growth monitoring participated in the study. Sixteen (16) IDIs and seven FGDs were conducted. Upon analysis of data, three main categories that explain the experiences and perceptions of women on postnatal care services utilization were generated. These categories are women’s experiences on postnatal care services utilization; perceived benefits of postnatal care services utilization, and, perceived barriers towards PNC services utilization. Women had negative experience and perceptions regarding PNC services utilization and they did not understand the advantages of PNC services to them, except for their children. Conclusion Women’s negative perceptions on PNC services utilization were revealed. Women did not understand the benefits of PNC services to them, except for their children. Barriers such as health systems, socio economic and cultural factors also affected PNC utilization. The government should improve PNC services through health education, promotion interventions aiming at PNC utilization. Improvements should address the availability and accessibility of services and importance of PNC services for both mother and her newborn in reducing maternal and newborn morbidity and mortality during postnatal period. Key words: Experiences, Perceptions, Postnatal Care, Nachingwea District, newborn.